Mind your language: why the language used to describe children's SEMH needs matters. Issue 3 (23rd February 2022) - Stanbridge, Joanna; Mercer, Emma
ABSTRACT: There are well-documented situational factors which correspond to risks of exclusion and mental health difficulties. However, in education policy, factors relating to exclusion and mental health needs are often attributed to dispositional, within-person factors rather than situational factors, or even wider systemic factors which may contribute to the situations in which difficulties occur. There is also a great deal of evidence that the language of description has a significant impact on how issues are perceived and responded to. The following study aimed to explore the language used to describe concerns about children and young people's social, emotional and mental health needs on referral forms into a Local Authority SEND Support service. Thematic analysis identified a variation in how needs were described, including within themes of 'What?' the behaviour was, 'Why?' it was occurring and a 'So What?' factor in terms of implications. The following article concludes that the language used to describe behaviours causing concern can have an important impact on how the behaviours are framed, and therefore responded to, and argues for avoidance of language which predisposes within-person accounts of behaviours at the expense of the situational and systemic interpretations which need addressing in order to facilitate inclusive responses.